Increased Serum Levels of Mesencephalic Astrocyte-Derived Neurotrophic Factor in Subjects With Parkinson’s Disease - Galli, Emilia; Planken, Anu; Kadastik-Eerme, Liis; Saarma, Mart; Taba, Pille; Lindholm, Päivi (Frontiers in Neuroscience, 2019)
Background: Mesencephalic astrocyte-derived neurotrophic factor (MANF) and cerebral dopamine neurotrophic factor (CDNF) promote the survival of midbrain dopamine neurons in animal models of Parkinson’s disease (PD). However, little is known about endogenous concentrations of MANF and CDNF in human PD patients, and their relation to PD pathogenesis. Our main objective was to study whether circulating concentrations of MANF and CDNF differ between PD patients and controls, and if they correlate with clinical parameters. Levels of circulating CDNF were studied for the first time. Methods: MANF and CDNF levels were measured from serum samples of 34 PD patients and 35 controls using validated in-lab-designed ELISAs. MANF and CDNF mRNA levels in whole blood samples of 60 PD patients and 30 controls were measured by qRT-PCR. MANF concentrations in different blood cell types were measured by ELISA. Results: Circulating MANF concentrations were significantly higher in PD patients compared to controls (P<0.001) and were positively correlated with Beck Depression Inventory (BDI) depression rating. MANF protein was present in blood cells, however, MANF mRNA levels in the blood did not differ between PD patients and controls (P=0.44). The mean concentration of serum CDNF was 33 pg/ml in the controls. CDNF levels were not altered in PD patients (P=0.25). Conclusions: MANF but not CDNF level was increased in the blood of PD patients. It would be interesting to examine the blood level of MANF from early stage PD patients in future studies to test whether MANF can be used as a clinical marker of PD.